Kaolin and salicylic acid alleviate summer stress in rainfed olive orchards by modulation of distinct physiological and biochemical responses - Brito, Cátia (2018)
In a changing world, the search for new agronomic practices that help crops to maintain and/or increase yields and quality is a continuous challenge. We aim to evaluate kaolin (KL) and salicylic acid (SA) effectiveness as summer stress alleviating agents through physiological, biochemical and immunohistochemical analysis. Olive trees (Olea europaea L. cv. Cobrançosa) grown under rainfed conditions were sprayed with 5% KL and 100 μM SA, at the beginning of summer, during two consecutive years. KL enhanced relative water content (RWC), stomatal conductance (gs) net photosynthesis (A) and leaf indole-3-acetic acid (IAA) signal, and decreased leaf sclerophylly, secondary metabolites and non-structural carbohydrates accumulation and abscisic acid (ABA).The trees treated with SA showed changes on IAA and ABA dynamics, and an enhancement in RWC, gs, A, soluble proteins, and leaf P and Mg concentrations during the summer. Notably, KL and SA also allowed a faster restauration of the physiological functions during stress relief. In sum, KL and SA foliar sprays alleviated the negative effects induced by summer stress in olive trees performance, by modulation of distinct physiological and biochemical responses.